THE INFLUENCE OF SELF-CONGRUITY ON CUSTOMER LOYALTY OF COFFEE SHOPS: EVIDENCE FROM GLOBAL-CHAIN AND LOCAL-CHAIN COFFEE SHOPS IN INDONESIA - Anjani, Dela; Dewi, Ike Janita (ASEAN Marketing Journal, 2021)
Manuscript type: Research Paper Research Aims: This paper seeks to examine the concept of “self-congruity” and its direct and indirect impacts on consumer loyalty of global versus local coffee shops. Design/methodology/approach: The study is a quantitative study using online survey on 400 respondents, which were distributed evenly to consumers of Starbucks (as a global coffee shop) and Anomali Coffee (as a local coffee shop in Jakarta, Indonesia). This paper employs Structural Equation Modelling (SEM) to study the relationships amongst variables. Research Findings: Results of the research show that generally self-congruity has a positive direct and indirect effect on customer loyalty. Theoretical Contribution/Originality: The research conveys that self-congruity consistently predicts consumer loyalty in various research settings, while environment perception, service perception, product perception, and price perception can influence consumer loyalty in different manners depending on the research context. The research contexts studied (global versus local coffee shops) also contributes to the discussion of globalization effects. Practitioner/Policy Implications: Life style products should develop strategies to match the product’s concepts with those of consumer values, particularly with regards to products with global versus local images. Furthermore, managers should pay attention to their pricing strategies where price perception can influence consumer loyalty. Research limitation/Implications: This study overlooks stages in the consumer’s purchase decision process where self-congruity can particularly affect a certain stage to finally result in consumer loyalty